URINA BOVINA E SEUS EFEITOS NO DESENVOLVIMENTO E PRODUÇÃO FINAL EM TRIGO (TRIRICUM AESTIVUM L.) - Oliveira, Juliana M. d.; Soares, Rômulo D.; Valentini, Ana P. F.; Wagner, Juliano F.; Gaviraghi, Fernando; Schwertner, Diogo V.; Garcia, Dagmar C.; Quadros, Valmir J. d.; Silva, Jose A. G. d. (Salão do Conhecimento, 2013)
Resumo